Fresnel incoherent correlation holography with single camera shot - Vijayakumar Anand (Institue of Optics and Electronics, Chinese Academy of Sciences, 2020)
Fresnel incoherent correlation holography (FINCH) is a self-interference based super-resolution three-dimensional imaging technique. FINCH in inline configuration requires an active phase modulator to record at least three phase-shifted camera shots to reconstruct objects without twin image and bias terms. In this study, FINCH is realized using a randomly multiplexed bifocal binary diffractive Fresnel zone lenses fabricated using electron beam lithography. The object space is calibrated by axially scanning a point object along the optical axis and recording the corresponding point spread holograms (PSHs). An object is mounted within the calibrated object space, and the object hologram was recorded under identical experimental conditions used for recording the PSHs. The image of the object at different depths was reconstructed by a cross-correlation between the object hologram and the PSHs. Application potential including bio-medical optics is discussed.